2019
DOI: 10.1007/s00401-019-02088-8
|View full text |Cite
|
Sign up to set email alerts
|

The histomolecular criteria established for adult anaplastic pilocytic astrocytoma are not applicable to the pediatric population

Abstract: Pilocytic astrocytoma (PA) is the most common pediatric glioma, arising from a single driver MAPK pathway alteration. Classified as a grade I tumor according to the 2016 WHO classification, prognosis is excellent with a 10-year survival rate > 95% after surgery. However, rare cases present with anaplastic features, including an unexpected high mitotic/proliferative index, thus posing a diagnostic and therapeutic challenge. Based on small histomolecular series and case reports, such tumors arising at the time o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…As a consequence of their low frequency, paediatric brain tumours are often categorized according to their histological similarities to the more frequent adult counterparts, irrespective of possible biological differences. This is particularly problematic for malignancy assessment of paediatric glial tumours and can result in an over estimation of malignancy for some patients as exemplified by a subset of paediatric glioblastoma and anaplastic pilocytic astrocytoma . On top of this, the consequences of a misdiagnosis are particularly grave in the paediatric context, for example the application of an unnecessary brain irradiation due to an overestimation of the malignancy of a glioma may lead to lifelong cognitive, endocrine and cerebral vascular dysfunction as well as the risk of radiation induced secondary brain tumours .…”
Section: The Development Of Dna Methylation‐based Brain Tumour Classimentioning
confidence: 99%
See 3 more Smart Citations
“…As a consequence of their low frequency, paediatric brain tumours are often categorized according to their histological similarities to the more frequent adult counterparts, irrespective of possible biological differences. This is particularly problematic for malignancy assessment of paediatric glial tumours and can result in an over estimation of malignancy for some patients as exemplified by a subset of paediatric glioblastoma and anaplastic pilocytic astrocytoma . On top of this, the consequences of a misdiagnosis are particularly grave in the paediatric context, for example the application of an unnecessary brain irradiation due to an overestimation of the malignancy of a glioma may lead to lifelong cognitive, endocrine and cerebral vascular dysfunction as well as the risk of radiation induced secondary brain tumours .…”
Section: The Development Of Dna Methylation‐based Brain Tumour Classimentioning
confidence: 99%
“…Several studies have demonstrated that tumours with a more benign clinical course and molecular profiles of more indolent entities such as pilocytic astrocytomas or pleomorphic xanthoastrocytomas may frequently be identified among series of histological glioblastomas . A recent study further demonstrated that paediatric cases diagnosed as anaplastic pilocytic astrocytoma are an extremely heterogeneous group . The majority of samples represent molecular pilocytic astrocytomas and only rarely molecular glioblastomas or anaplastic astrocytomas with piloid features .…”
Section: Methylation Profiling Of Established Paediatric Brain Tumourmentioning
confidence: 99%
See 2 more Smart Citations
“…Diagnosis was "unusual glioneuronal tumor with histological features of anaplasia". Central review was performed under the framework of the national RENOCLIP-LOC network and DNA-methylation profiling was performed using an EPIC array (Integragen, Evry, France) as previously described [10]. The raw IDAT files were uploaded to https://www.molecularneuropathology.org for supervised analysis using the Random Forest methylation class prediction algorithm, and copy number profiles were obtained as previously described [11].…”
Section: Casementioning
confidence: 99%